Effects of various milk powders on main quality parameters of cocoa butter substitute-based chocolate. (April 2023) - Konar, Nevzat; Genc Polat, Derya; Dalabasmaz, Sevim; Erdogan, Melih; Sener, Sinem; Kelleci Sarıkaya, Ebru
Abstract: Optimal conditions for formulation of cocoa butter substitute (CBS)-based milk chocolate produced in a ball mill with hydrogenated palm kernel oil stearin as CBS were defined using a D-optimal mixture design. In the formulation of chocolate samples, various amounts of whole milk powder, skimmed milk powder and demineralised whey powder were used and their effect on physico-chemical, colour, texture, and sensory properties were investigated. The fitted models demonstrated significant effects of independent variables on various quality parameters. Optimum formulation for selected parameters to maximise taste and minimise whole milk powder content as well as reduce costs were determined. Moreover, the optimum formulation was produced to validate the optimum model. Results of the validation were consistent with the findings of the model study. Furthermore, the approach used in this work could be employed to develop strategies to produce CBS-based milk chocolate with lower costs and various quality properties.